Sustaining the Ngerebong Tradition: Reinterpreting Rituals in an Interfaith and Intercultural Context - Nindya, Ni Made Ayu Nindya Damayanti; Mudzakkir, Moh.; Fauzi, Agus Machfud; Syaifullah, Khalid (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2026)
This study investigates the sociological dynamics of the Ngerebong tradition in Kesiman, focusing on interreligious and intercultural interactions within a Hindu-majority community. It aims to understand how ritual practices serve as a medium for social negotiation and cultural adaptation in a pluralistic environment. Using a qualitative approach, the research combines field observation, interviews, and document analysis to explore symbolic expressions and social participation across religious groups. The findings reveal that the Ngerebong is not only a sacred ceremony but also a communal space where diverse identities engage in shared cultural experiences. Non-Hindu involvement in the ritual reflects openness and mutual respect, contributing to inclusive social cohesion. The study identifies shifts in symbolic meaning and ritual function, shaped by modernization, tourism, and digital media. These changes demonstrate the community’s capacity to reinterpret tradition while preserving its spiritual essence. The analysis applies functionalist and conflict theory to explain how ritual fosters solidarity and reveals latent tensions. Ultimately, the research concludes that the Ngerebong operates as a living tradition that sustains cultural identity and promotes intergroup harmony. It offers a model for understanding how local rituals can support integration in multicultural societies, with implications for promoting sustainable cultural practices, strengthening interfaith dialogue, guiding policy frameworks that encourage social cohesion, and future research on the resilience of traditions under globalization.